Advanced proposals to improve advanced directives in Portugal - Macedo, João Carlos Gama Martins (2022)
This article describes the current state of Advance Directives (living wills and/or attorney health care in the event of inability to express one) in Portugal. It investigates the reasons for the low number of registered advance directives and proposes two ways to increase citizens' adherence: Setting up a counselling in the national health system and the standard form.